PENCATATAN PERKAWINAN DALAM PERPSPEKTIF MASLAHAH AL-GHAZALI - Faruq, Ahmad (Irtifaq, 2016)
Marriage in UU No. 1/1974 is referred to as a mental bond between a man and a woman as a husband and wife with the aim of forming a happy and eternal family. The ultimate goal of marriage is essentially happiness. Happiness means the benefit or justice for all family members that arise due to the marriage relationship. Marriage recording aims to realize marital order in society. It is an attempt to protect the dignity and sanctity of marriage, and more particularly for women (wives) in domestic life. If according to the Law of marriage must be registered and as a proof of registration it is a Marriage Certificate, then it is a form of state protection to the citizens to obtain legal certainty and rights of both parties husband and wife and child. Recording of marriage will give mashlahah impact to all parties, as the rule of fiqh which reads tasharruf al imam ala al ra'iyah manuth bi al mashlahahKeyword : perkawinan, akta nikah dan mashlahat